PEMERIKSAAN BAHAN TAMBAHAN PANGAN BERBAHAYA (BORAKS) PADA BAKSO DI KOTA GORONTALO - Syelomita Rahim; Fildzah istiqomah Dukalang; Alfian S Abas (Journal of Health, Technology and Science (JHTS), 2022)
Currently, the use of borax in food or food ingredients is very often carried out by several food manufacturers, such as meatballs, noodles, crackers and dried fish. The actual function of borax is that it is used by the non-food industry as a cleaning agent, wood preservative, soldering agent, antiseptic and cockroach control. This study aims to identify the borax content in the meatballs sold in Gorontalo City and to find a relationship between the knowledge and attitudes of traders towards the existence of the borax content in the meatballs they sell. The method in this study uses a qualitative approach with a descriptive research type. The type of data used is primary data in the form of obtained by conducting initial observations and interviews , laboratory tests accompanied by documentation, as well as secondary data in the form of literature data and government policies regarding food additives. The number of samples is 10 samples, taken from 10 Meatball seller in Gorontalo City . The results of the study were that eight samples of meatballs were negative or did not contain borax and there were two samples of meatballs that were positive or contained borax. This was indicated by the color change on the curcumin paper turning brown if the result was positive and if the result was negative, the curcumin paper did not change color .